Beyond the Cholinergic Hypothesis: Do Current Drugs Work in Alzheimer's Disease? - Martorana, Alessandro (CNS Neurosci Ther, 2010)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by memory and cognitive loss, and represents the leading cause of dementia in elderly people. Besides the complex biochemical processes involved in the neuronal degeneration (formation of senile plaques containing Aβ peptides, and development of neurofibrillary tangles), other molecular and neurochemical alterations, like cholinergic deficit due to basal forebrain degeneration, also occur. Because acetylcholine has been demonstrated to be involved in cognitive processes, the idea to increase acetylcholine levels to restore cognitive deficits has gained interest (the so‐called cholinergic hypothesis). This has led to the development of drugs able to prevent acetylcholine hydrolysis (acetylcholinesterase inhibitors). However, the analysis of clinical efficacy of these drugs in alleviating symptoms of dementia showed unsatisfactory results. Despite such critical opinions on the efficacy of these drugs, it should be said that acetylcholinesterase inhibitors, and for some aspects memantine also, improve memory and other cognitive functions throughout most of the duration of the disease. The pharmacological activity of these drugs suggests an effect beyond the mere increase of acetylcholine levels. These considerations are in agreement with the idea that cognitive decline is the result of a complex and not fully elucidated interplay among different neurotransmitters. The role of each of the neurotransmitters implicated has to be related to a cognitive process and as a consequence to its decline. The current review aims to highlight the positive role of cholinergic drugs in alleviating cognitive deficits during wake as well as sleep. Moreover, we suggest that future therapeutic approaches have to be developed to restore the complex interplay between acetylcholine and other neurotransmitters systems, such as dopamine, serotonin, noradrenaline, or glutamate, that are likely involved in the progressive deterioration of several cognitive functions such as attention, memory, and learning.